2012
DOI: 10.1016/j.beproc.2011.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Intertemporal choice in lemurs

Abstract: Different species vary in their ability to wait for delayed rewards in intertemporal choice tasks. Models of rate maximization account for part of this variation, but other factors such as social structure and feeding ecology seem to underly some species differences. Though studies have evaluated intertemporal choice in several primate species, including Old World monkeys, New World monkeys, and apes, prosimians have not been tested. This study investigated intertemporal choices in three species of lemur (blac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
37
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 50 publications
2
37
0
Order By: Relevance
“…The strong relationship between waiting times and allometry matches a previous result demonstrating that waiting times correlated positively with body mass [3]. This result supports the adaptive nature of the allometric scaling hypothesis because waiting times scale with two factors rspb.royalsocietypublishing.org Proc.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The strong relationship between waiting times and allometry matches a previous result demonstrating that waiting times correlated positively with body mass [3]. This result supports the adaptive nature of the allometric scaling hypothesis because waiting times scale with two factors rspb.royalsocietypublishing.org Proc.…”
Section: Discussionsupporting
confidence: 88%
“…Stevens & Mü hlhoff [3] showed that waiting times increased with mean species body mass. This could occur because metabolism allometrically scales with body size: species with lower body mass also tend to have faster metabolic rates [14 -16].…”
Section: Introductionmentioning
confidence: 99%
“…(B) In most implementations, a postreward buffer is added to make sure that the trial lengths for both options are equivalent; otherwise, the subject can advance to the next trial sooner. This postreward buffer is identified here as a potentially problematic element of the design of the task Rilling, 1965;Rachlin & Green, 1972;Rosati et al, 2007;Siegel & Rachlin, 1995;Snyderman, 1983;Stephens & Anderson, 2001;Stevens & Mühlhoff, 2012). Interestingly, these findings extend to normally patient humans in some contexts.…”
Section: The Intertemporal Choice Taskmentioning
confidence: 62%
“…Moreover, other species do show preferences for the smaller, immediate reward in intertemporal choice tasks when the larger reward is delayed for even short periods, on the order of 10-20 s (Stevens & Stephens, 2008). This includes cotton-top tamarins (Saguinus oedipus), marmosets (Callithrix jacchus), and several lemur species tested in quite similar contexts with visible food rewards (Stevens, Hallinan, & Hauser, 2005;Stevens & Muhlhoff, 2012). Given that great apes show much more robust inhibitory control over prepotent reaching responses compared to other primates (see Maclean et al, 2014, for a large cross-species comparison), it is difficult to see how this pointing explanation could account for this complete set of results.…”
mentioning
confidence: 99%